2013
DOI: 10.12720/jomb.2.3.163-167
|View full text |Cite
|
Sign up to set email alerts
|

Peroxidase Activity in Native and Callus Culture of Moringa Oleifera Lam

Abstract: In vitro Moringa oleifera Lam. seedlings were successfully produced through seed culture on Murashige & Skoog (MS) agar medium containing 3% (w/v) sucrose and 0.2% (w/v) Gelrite TM in the absence of growth regulators under 1,500 lux of light density, 16 hour photoperiod light at temperature of 25 ± 2°C. Shoot-derived callus and rootderived callus of M. oleifera were established via culture of shoot and root on the MS medium supplemented with 0.5 mg/l of 2,4-dichlorophenoxy acetic acid (2,4-D) in the dark at 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 12 publications
0
8
1
Order By: Relevance
“…Callus, mainly comprising masses of undifferentiated cells, is good starting material for in vitro manipulation (Oriabi, 2013). But these results was disagreement with those obtained by Shank et al, (2013) who reported that MS medium supplemented with 0.5mg/l of 2,4-D was the most effective medium for callus induction of M. oleifera with 100% of callus induction from week-3 after culturing of shoot, Figure 1 showing the callus mass of M. oleifera which grown on MS medium after two subcultures. Results in table 3 described the changes in the weight of animals based on varying extract doses during the 15 days of treatment and showed that the body weight of mice significantly increased in the positive control group and those treated with 20, 40 and 80% of M. oleifera leaves or callus extracts compared with negative control which was significantly decreased with increasing days of treatment, these results was agreement with those obtained by Aja et al, (2013) who reported a significant (P<0.05) reductions in the mean body weight of rats in diabetic control compared to positive group while rats in treated groups showed significant (P<0.05) increase in their mean body weight compared to diabetic control group in work done earlier on antidiabetic effect of aqueous extract of Moringa oleifera and Bridelia ferruginea leaves in alloxan-induced diabetic albino rats.…”
Section: Resultscontrasting
confidence: 57%
“…Callus, mainly comprising masses of undifferentiated cells, is good starting material for in vitro manipulation (Oriabi, 2013). But these results was disagreement with those obtained by Shank et al, (2013) who reported that MS medium supplemented with 0.5mg/l of 2,4-D was the most effective medium for callus induction of M. oleifera with 100% of callus induction from week-3 after culturing of shoot, Figure 1 showing the callus mass of M. oleifera which grown on MS medium after two subcultures. Results in table 3 described the changes in the weight of animals based on varying extract doses during the 15 days of treatment and showed that the body weight of mice significantly increased in the positive control group and those treated with 20, 40 and 80% of M. oleifera leaves or callus extracts compared with negative control which was significantly decreased with increasing days of treatment, these results was agreement with those obtained by Aja et al, (2013) who reported a significant (P<0.05) reductions in the mean body weight of rats in diabetic control compared to positive group while rats in treated groups showed significant (P<0.05) increase in their mean body weight compared to diabetic control group in work done earlier on antidiabetic effect of aqueous extract of Moringa oleifera and Bridelia ferruginea leaves in alloxan-induced diabetic albino rats.…”
Section: Resultscontrasting
confidence: 57%
“…They found that the activity of peroxidase on the callus of all explants was higher than that of the intact plant. Shank et al [54] examined the peroxidase activity in the calli of different explants of Moringa oleifera. They also showed that the enzyme activity was higher in callus than in plant.…”
Section: Discussionmentioning
confidence: 99%
“…Moringa oleifera have the valuable effect as medicine, nutrition, water management and so on [15]. Leaves, fruits, roots of MO are used as vegetables [23] and source of vitamins [24,25]. Other sides, various parts of MO such as stem, bark, and roots have antimicrobial activities [26,27].…”
Section: Introductionmentioning
confidence: 99%